When the file is in the witness: documentation in scenarios of chronic insecurity (2012)
Through an exchange between members of community organizations documenting human rights violations in northwest Colombia and northern Uganda, this article examines strategies for building memory where an individual or a group creates a safe social space to give testimony and re-story-telling acts of violence or resistance. In scenarios of chronic insecurity, such acts constitute a reservoir of living documents that preserve the memories, testify, reduce impunity and convey the sense or "veracity" of the survivors. The living file overturns conventional assumptions about what is a document or testimony in the field of transitional justice. It also introduces new interdisci plinary tools with which to learn from and listen to survivors in a different way.